Cartilage organoids: an emerging platform for novel osteoarthritis therapies - Gao, Bimin; Chen, Zecai; Long, Yufeng; He, Feng; Gan, Donghao; Yi, Weihong; Xiao, Guozhi; Ren, Jiangdong; Qin, Lei (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is a chronic, multifactorial joint disorder characterized by the progressive degeneration and dysfunction of various joint tissues. Current treatments primarily focus on symptom management, offering limited success in halting cartilage degradation or repairing damaged tissues. Consequently, there is a pressing need for innovative therapeutic strategies aimed at cartilage regeneration and structural repair. Over the past 2 decades, cartilage organoids have emerged as a promising alternative for OA treatment. Due to their unique regenerative properties, cartilage organoids provide a versatile platform for various applications in OA research and therapy, including in vitro disease modeling, drug screening, regenerative medicine, and biomechanical studies. This review summarizes current research progress and insights into OA pathogenesis and therapeutic approaches, explores the development of cartilage organoid technologies with a focus on organoid constructions and different methodologies, and discusses the future applications of cartilage organoids as essential in vitro models for drug screening and personalized therapies for OA studies and treatment.